PENGEMBENGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS PODCAST PADA MATA PELAJARAN SEJARAH DI SMA ISLAM AL-FALAH JAMBI - Indriyanti, Novia; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
This research and development departs from the problems that occurred at Al-Falah Islamic High School Jambi where the media used was less varied. Learning media can be an alternative in the problems that occur. This study aims to produce learning media products, namely podcast-based audio-visual media and apply it to class X history learning at Al-Falah Islamic High School Jambi. The method used in this research is ADDIE which has five stages, namely: 1. Analysis (Analyze), 2. Design (Design), 3. Development (Development), 4. Implementation (Implementation), and 5. Evaluation (Evaluation). The research was conducted at Al-Falah Islamic High School Jambi with Research Subjects Class X IPA 1 students, totaling 3 people for individual trials, 10 small group trials, and 32 people in field trials. This research has produced a product in the form of podcast-based audio-visual media with Hindu-Buddhist material. The developed media is then validated by the validator, including the validation of media experts and material experts. the results of the first stage of validation by media experts obtained a value of 59% and carried out